2015
DOI: 10.3174/ajnr.a4370
|View full text |Cite
|
Sign up to set email alerts
|

CTP in Transient Global Amnesia: A Single-Center Experience of 30 Patients

Abstract: BACKGROUND AND PURPOSE:Medial temporal lobe abnormalities on DWI and functional imaging are occasionally observed in patients with transient global amnesia. We used CTP to study these patients during or briefly after resolution of their amnesic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…Our research group already studied hypoperfusion characteristics in patients with TIA who underwent PCT, 15 and we previously demonstrated that they might be useful in differential diagnosis from other conditions, including transient global amnesia or posterior reversible encephalopathy syndrome. 16 , 17 Similarly, in the present study, we suggest that a CTP-quantitative analysis might detect a moderate hypoperfusion pattern in the cerebral regions during MA, compatible with aura symptoms, which could help in distinguishing from TIA.…”
Section: Discussionsupporting
confidence: 77%
“…Our research group already studied hypoperfusion characteristics in patients with TIA who underwent PCT, 15 and we previously demonstrated that they might be useful in differential diagnosis from other conditions, including transient global amnesia or posterior reversible encephalopathy syndrome. 16 , 17 Similarly, in the present study, we suggest that a CTP-quantitative analysis might detect a moderate hypoperfusion pattern in the cerebral regions during MA, compatible with aura symptoms, which could help in distinguishing from TIA.…”
Section: Discussionsupporting
confidence: 77%
“…Retrograde amnesia refers to forget past events, and new memories can be formed. TGA refers to sudden anterograde amnesia with or without retrograde amnesia, lasting less than 24 hours, without other clinical neurological dysfunction (1,2). The current diagnosis of TGA mainly refers to the standard established by Hodges et al (3), including confirmed by witnesses; anterograde memory loss; clear consciousness; no other cognitive impairments except for memory impairment; complete insight; no positive signs on neurological physical examination, and no recent history of brain trauma and seizures.…”
Section: Discussionmentioning
confidence: 99%